Determination of carotenoid(s) composition in intact plant, callus and shoot cultures of Ruta angustifolia (L.) Pers. - Mohd. Zaifuddin, Fatimah Azzah; Mohd Hassan, Norazian; Othman, Rashidi (2011)
Researches concerning antioxidants are extensively studied nowadays. Antioxidants are well known to be associated with reduction in cancer incidence since they act against deteriorative effects of free radicals. These antioxidants include the yellow-to-red coloured pigments known as carotenoids, are essential for betterment in human immunity. Carotenoids can be found abundantly in dark green vegetables and also yellow, orange and red coloured fruits. They have to be taken up from daily diets since they cannot be produced by human biological system. Some carotenoids serve as pro-vitamin A that supple human visual and skin health. In this study, we aim to determine the carotenoid(s) content of Ruta angustifolia and their profile in the intact plant, callus and shoot cultures. The callus cultures were induced from stem explants and subsequently subcultured until the calli successfully generated in vitro shoots. The carotenoids extracts from the plant tissues were analysed qualitatively and quantitatively by using UV spectrophotometry and HPLC. The result showed that there was significant difference in accumulation of carotenoid(s) among the plant sources and the most common carotenoids found were β-carotene and lutein. The intact plant showed the highest content of the carotenoids whilst the callus possess the least. The outcome of this study could be used for further manipulation of the in vitro cultures for the carotenoids production enhancement.